Article Structures: Moving from Printed to e-Dictionaries - Gouws, Rufus H. (Lexikos, 2014)
By means of an overview of certain aspects of article structures in printed dictionaries and with reference to some examples from e-dictionaries a number of features of article structures in e-dictionaries are discussed. Reference is made to the positioning of articles in article stretches and functional partial article stretches. Different structural components of articles, i.e. text segments, comments and search zones are distinguished. The increased role of data-identifying entries as a type of non-typographical structural indicator in e-dictionaries receives attention as well as the fact that the traditional division of an article in two comments, typically a comment on form and a comment on semantics, cannot merely be maintained. The value of the cohesion resulting from the use of comments in printed dictionaries is much more restricted in e-dictionaries. The use of search zones and rapid access to these zones have a much more important role in the article structure of e-dictionaries. In the planning of e-dictionaries provision needs to be made for a multi-layered article structure with screenshots that display the data in a variety of search zones. Access to these search zones goes via structural indicators in an opening or further screenshot. Provision needs to be made for one lemma to occur in a comprehensive article but also in a number of restricted articles that can be retrieved from the same database. Users should also have the opportunity to design their own user profile that will allow them to consult dictionary articles structured according to their specific needs. Keywords: article structure, comment, comprehensive article, data-identifying entry, e-dictionaries, item, multi-layered articles, non-typographical structural indicator, partial article stretch, restricted articles, screenshot, search zone, text segments, user profile